RETRACTED ARTICLE: SLFN5 promotes reversible epithelial and mesenchymal transformation in ovarian cancer - Qiao Ping Xu; Kui Deng; Zhen Zhang; Hongkai Shang (Journal of Ovarian Research)
Abstract Ovarian cancer is a disease with increasing incidence worldwide, and there is an urgent need for chemotherapy and biological targeted therapy. Epithelial-mesenchymal transformation (EMT) is an important initiation stage for tumor cells to acquire the ability to invade and metastasize. A growing number of findings suggest that human Schlafen family member 5(SLFN5) plays a key role in malignancy. However, the role of SLFN5 in ovarian cancer cells has not been fully elucidated. Samples were collected from patients with ovarian cancer diagnosed in Hangzhou First People's Hospital, and the expression of SLFN5 was detected by fluorescence quantitative PCR. The relationship between SLFN5 expression and the progression and malignancy of ovarian cancer was analyzed by using the expression profile data from the Cancer Genome Atlas (TCGA) database. The mRNA expression levels of SLFN5 related upstream and downstream signaling pathways were studied by fluorescence quantitative PCR. Silencing SLFN5 was performed by siRNA transfection. The expression of SLFN5 and transfer-related proteins was examined by Western blot. Transwell and wound healing experiments investigated the migration and invasion ability of ovarian cancer cells. TCGA database analysis results showed that in the population with high SLFN5 expression, compared with the group with low SLFN5 expression, OS was worse (P = 0.011). SLFN5 silencing had a significant inhibitory effect on EMT and invasion movement of ovarian cancer cells. RT-PCR method was used to detect the mRNA changes of SLFN5 in ovarian cancer tissue and adjacent tissue. It was found that the expression of SLFN5 in ovarian cancer tissue was increased, with a significant difference (P < 0.05). Together, these results suggest that SLFN5 may play a synergistic role in tumorigenesis and development of ovarian cancer cells, providing a potential target for future drug development for the treatment of ovarian cancer.